STRATEGI PEMASARAN ONLINE DAN OFFLINE PADA LAPAK MARIMAR SINTANG - Dewi Suryati (Jurnal Ekonomi dan Bisnis, 2023)
This research departs from the success of the Sintang marimar stalls in building their business from year to year, even though the location is not strategic, the Sintang marimar stalls are able to become stalls that are in great demand by the people of Sintang and its surroundings. It is proven that with the pandemic this stall remains stable. This research uses a qualitative approach and a field study type. Data collection techniques through interviews, observation and documentation. Data analysis uses an interactive analysis model which includes data reduction, data display, and verification/conclusion. The results of this study indicate that the online and offline marketing strategies carried out by Marimar Sintang stalls through a marketing mix include five of them: Products sold by Marimar Sintang Stalls are halal products, and fresh, prices are The Marimar Sintang Stalls offer vary depending on the quality, the place used is not strategic, even so the Marimar Sintang Stalls are still of great interest to consumers who love seafood, frozen food, etc. Promises (Promises) that are kept both by the owner and by employees for the convenience of consumers. Promotions carried out through social media. The inhibiting factors in online and offline marketing at these stalls are the stalls that are not strategic, weather changes. While the supporting factors are the existence of products that are always fresh and halal, the prices offered vary, buying online and offline there is a difference in price for the buyer. Consistent promotions.